Character Design Of 2-Dimensional Animation About Natural Disasters For 10-12 Years Old - Bunga Cadika Mayang Andrasya (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2024)
This research aims to design a 2-dimensional animation that focuses on education about natural disasters, especially for elementary school children aged 10-12 years. By utilizing design principles, this animation is developed to provide information that is easy to understand and attracts children's attention. The design method involves a literature study on the types of natural disasters, learning characteristics of elementary school children, and animation principles. After that, the storyboard process and character development were carried out in accordance with the needs of children's education about natural disasters. The result of this research is a 2-dimensional animation designed creatively and informatively, presenting material about natural disasters such as the types, and how to take shelter. This animation is expected to increase elementary school children's understanding of the dangers of natural disasters, as well as provide basic knowledge about actions that can be taken to reduce the risk and damage caused by natural disasters.